Kontribusi Mahasiswa KPM INSURI dalam Meningkatkan Mutu Pembelajaran di Madrasah Diniyah Desa Ngrogung Ngebel Ponorogo - Muih Hamim Miftahul Khoiri; Nanik Setyowati (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Islamic education in rural areas, especially in madrasah diniyah, requires continuous innovation to improve the quality of learning and student enthusiasm. The Community Service Program (KPM) provides opportunities for Islamic Religious Education students to contribute to improving the quality of learning in Islamic educational institutions. This study aims to analyze the contribution of INSURI KPM students in improving the quality of learning at Madrasah Diniyah in Ngrogung Village, Ngebel District, Ponorogo Regency. This research uses a qualitative approach with field research methods through observation and interviews. The results showed that KPM students made significant contributions through the application of innovative learning methods, the use of interactive learning media, and varied teaching approaches that succeeded in increasing student enthusiasm and learning outcomes. The increase in learning quality can be seen from the active participation of students in learning, increased understanding of religious material, and positive responses from teachers and the community. The KPM program proves to be effective as a bridge between academic knowledge and the needs of Islamic educational institutions in rural areas.